Transition radiation of a relativistic electron bunch on a semi-infinite metal cylinder - Balakirev, V.A.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2021)
Transition radiation of a relativistic electron bunch, which arises when it collides with the end face of a semi-infinite ideally conducting cylinder, is considered. An electron bunch moves along the axis of a semi-infinite cylinder. Expressions for the field strength of electromagnetic radiation in the wave zone are obtained. The influence of the guiding properties of an ideally conducting cylinder on the directional diagram of the transition radiation is investigated.